Differential roles of high gamma and local motor potentials for movement preparation and execution. Issue 2 (2nd April 2016) - Gunduz, Aysegul; Brunner, Peter; Sharma, Mohit; Leuthardt, Eric C.; Ritaccio, Anthony L.; Pesaran, Bijan; Schalk, Gerwin
Abstract : Determining a person's intent, such as the planned direction of their movement, directly from their cortical activity could support important applications such as brain-computer interfaces (BCIs). Continuing development of improved BCI systems requires a better understanding of how the brain prepares for and executes movements. To contribute to this understanding, we recorded surface cortical potentials (electrocorticographic signals; ECoG) in 11 human subjects performing a delayed center-out task to establish the differential role of high gamma activity (HGA) and the local motor potential (LMP) as a function of time and anatomical area during movement preparation and execution. High gamma modulations mostly confirm previous findings of sensorimotor cortex involvement, whereas modulations in LMPs are observed in prefrontal cortices. These modulations include directional information during movement planning as well as execution. Our results suggest that sampling signals from these widely distributed cortical areas improves decoding accuracy.